PENGARUH MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA SD: ANALISIS BERDASARKAN PERBEDAAN GENDER - Mufli Yahya; Nila Kesumawati; Nurlela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low scores of students in mathematics occur because students are less active in learning and they consider mathematics a difficult subject. The method used in this research is an experimental method, specifically True Experimental Design with a Posttest Only-Control Design. The population used in this study consisted of all 288 students of SD Negeri 16 Palembang. The samples taken were 28 students from class IV A as the experimental group who were given treatment in the form of audio-visual media, and 25 students from class IV B as the control group who were not given treatment. Data collection techniques used essay tests to measure students' mathematical concept comprehension ability. Data analysis techniques used Two-Way ANOVA test. The results of the analysis showed that (1) there is an effect of using audio-visual media on mathematical concept comprehension ability in students of SD Negeri 16 Palembang; (2) there is a difference in mathematical concept comprehension ability based on gender in students of SD Negeri 16 Palembang; (3) There is no interaction between audio-visual media and gender on mathematical concept comprehension ability in students of SD Negeri 16 Palembang